A Review of Graduate Attributes in the Oman Authority for Academic Accreditation and Quality Assurance of Education (OAAAQAE's) Quality Audit Reports - Zulaikha Talib Al-Saadi; Holi Ibrahim Holi Ali (Gulf Education and Social Policy Review)
Abstract With the growing importance of the development of graduate attributes (GAs) in higher education, higher education institutions (HEIs) are emphasizing which GAs their graduates attain as part of their mission, vision, and core values, and are required to describe and document how their programs contribute to the development and promotion of those attributes. Qualitative data were collected from 12 quality audit reports from the Oman Authority for Academic Accreditation and Quality Assurance of Education (OAAAQA). This paper identifies the OAAAQA's key areas of interest and their importance in ensuring quality in college-preparedness programs, as well as making recommendations for future audits. The paper seeks to: (1) highlight the most salient issues that have been raised in their reports regarding GAs and (2) make some suggestions so that HEIs in Oman can establish and implement GAs more effectively to meet both the OAAAQA's expectations and good international practices. Following a data-driven systematic qualitative content analysis (QCA) of the QA reports, four main categories emerged regarding the GAs. Student learning objectives should be aligned with GA development, while stakeholders' awareness of these attributes should be raised. Additionally, there is a need for an appropriate evaluation mechanism for GAs to be conducted in a systematic and timely manner. Moreover, GAs should be explicitly assessed and benchmarked based on the feedback obtained from relevant stakeholders. Finally, both internal and external stakeholders should be involved in the GA development and review process.